Biosynthesis of Indole Diterpene Lolitrems: Radical‐Induced Cyclization of an Epoxyalcohol Affording a Characteristic Lolitremane Skeleton. (18th August 2020) - Jiang, Yulu; Ozaki, Taro; Harada, Mei; Miyasaka, Tadachika; Sato, Hajime; Miyamoto, Kazunori; Kanazawa, Junichiro; Liu, Chengwei; Maruyama, Jun‐ichi; Adachi, Masaatsu; Nakazaki, Atsuo; Nishikawa, Toshio; et al.
Abstract: Lolitrems are tremorgenic indole diterpenes that exhibit a unique 5/6 bicyclic system of the indole moiety. Although genetic analysis has indicated that the prenyltransferase LtmE and the cytochrome P450 LtmJ are involved in the construction of this unique structure, the detailed mechanism remains to be elucidated. Herein, we report the reconstitution of the biosynthetic pathway for lolitrems employing a recently established genome‐editing technique for the expression host Aspergillus oryzae . Heterologous expression and bioconversion of the various intermediates revealed that LtmJ catalyzes multistep oxidation to furnish the lolitrem core. We also isolated the key reaction intermediate with an epoxyalcohol moiety. This observation allowed us to establish the mechanism of radical‐induced cyclization, which was firmly supported by density functional theory calculations and a model experiment with a synthetic analogue. Abstract : Lolitrem B is a tremorgenic indole diterpene produced by a fungal endophyte. During its biosynthesis, LtmJ, a cytochrome P450 monooxygenase, catalyzes a 3‐step oxidation of a diprenylated intermediate to construct the 5/6 bicyclic system. Given the reaction intermediate with an epoxyalcohol, a radical‐induced cyclization mechanism, supported by density functional theory calculations and a model experiment, is proposed.